2008
DOI: 10.1002/0471142700.nc0806s32
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Dimeric 2‐Amino‐1,8‐Naphthyridine and Related DNA‐Binding Molecules

Abstract: The synthetic protocols for dimeric 2-amino-1,8-naphthyridine and related compounds are described in this unit. These compounds represent a novel class of compounds that bind selectively to mismatched base pairs. The compounds consist of two main components: the heterocycles and a linker. Connecting two heterocycles by a linker was found to modulate the binding selectivity. This unit describes the synthesis of dimeric 2-amino-1,8-naphthyridine (which binds to the G-G mismatch), naphthyridine-azaquinolone (for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…[11] We have reported mismatch binding ligands that can stabilize the hairpin secondary structures of dA C H T U N G T R E N N U N G (CAG) n and d-A C H T U N G T R E N N U N G (CGG) n repeats. [12,13] Among the mismatch binding ligands, naphthyridine carbamate dimer (NCD), consisting of two Nalkyloxycarbonyl-2-amino-7-methyl-1,8-naphthyridine heterocycles as a recognition element for nucleotide bases (Scheme 1), strongly bound to dA C H T U N G T R E N N U N G (CGG) n repeats. A surface plasmon resonance (SPR) assay of NCD binding to the TRS by means of an immobilized-NCD sensor showed that NCD bound not only to dA C H T U N G T R E N N U N G (CGG) n but also to dA C H T U N G T R E N N U N G (GAA) n , dA C H T U N G T R E N N U N G (CAG) n , dA C H T U N G T R E N N U N G (GCC) n , and dA C H T U N G T R E N N U N G (CTG) n repeats with decreased efficiency (Figure 1 a).…”
Section: Introductionmentioning
confidence: 99%
“…[11] We have reported mismatch binding ligands that can stabilize the hairpin secondary structures of dA C H T U N G T R E N N U N G (CAG) n and d-A C H T U N G T R E N N U N G (CGG) n repeats. [12,13] Among the mismatch binding ligands, naphthyridine carbamate dimer (NCD), consisting of two Nalkyloxycarbonyl-2-amino-7-methyl-1,8-naphthyridine heterocycles as a recognition element for nucleotide bases (Scheme 1), strongly bound to dA C H T U N G T R E N N U N G (CGG) n repeats. A surface plasmon resonance (SPR) assay of NCD binding to the TRS by means of an immobilized-NCD sensor showed that NCD bound not only to dA C H T U N G T R E N N U N G (CGG) n but also to dA C H T U N G T R E N N U N G (GAA) n , dA C H T U N G T R E N N U N G (CAG) n , dA C H T U N G T R E N N U N G (GCC) n , and dA C H T U N G T R E N N U N G (CTG) n repeats with decreased efficiency (Figure 1 a).…”
Section: Introductionmentioning
confidence: 99%
“…[10] An improved synthesis of 15 is shown in Scheme 2. The key step is the rearrangement of the N-oxide 11 to the corresponding hydroxymethyl derivative 12.…”
Section: Resultsmentioning
confidence: 99%
“…13,15,22 The selective binding of ND to the GG mismatch, among seven other mismatches, has been verified by examining the thermal stability of the mismatch-containing duplexes in the presence of ND. In general, ligand binding to DNA increases the thermal stability of the duplex, making the temperature required for denaturation of a duplex to a single strand higher than that in the absence of the ligand.…”
Section: Conceptual Model For Mismatch Recognitionmentioning
confidence: 96%
“…In this article, we describe the inside story of MBLs about the discovery, identifying the function, and the application in genomic science. 22 3. Recognition of Mismatched Base Pairs 3.1 GG Mismatch Recognition.…”
Section: Conceptual Model For Mismatch Recognitionmentioning
confidence: 99%